Composition and Ecology of the Macro-Zoobentos Community Feeding Group and the Relationship with the Water Quality of Lake Maninjau, West Sumatera - Adnan Yelka; Athosra Athosra; Petrizal Petrizal; Eni Kamal; Abdul Razak; Isril Berd (Pascasarjana, Universitas Negeri Padang, 2019)
Information on the ecological status of inland waters is important to know in the framework of management and conservation purposes, including the biota elements of the Macro-zoobenthos community. This study aims to determine the composition and ecology of feeding acro zoobenthos and its relation to the water quality of Lake Maninjau. Lake Maninjau is one of the priority lakes that has an important role both economically and ecologically. Data were collected from journal literacy. There are 34 types of acro zoobenthos with a low diversity index (H= 0.34-0.82). The distribution of each Taxa was less to nearly even (E= 0.30-0.93). The Macro-zoobenthos found belonged to Molluscs, Oligochaeta, EuHirudinea, Insect Larvae, and Crustaceans. Molluscs were the most abundant, spread over 70% of locations and dominated by Corbicula species. The highest abundance is in the Sigiran location. A total of 26 Taxa were characterized by temperature, TDS, and conductivity variables, while the other 8 were characterized by DO and ORP based on CCA results. The feeding Collector ecology group (especially the filter collector) dominates. This indicates that the waters of Lake Maninjau are rich in fine particulate organic matter (FPOM).